KARAKTERISASI KONSENTRAT TEMBAGA INDONESIA UNTUK DIKLAT PENINGKATAN NILAI TAMBAH TEMBAGA - Imelda Hutabarat (PPSDM Geominerba, 2017)
Indonesia many copper reserves which are spread in certain locations along the ‘ring of fire’, the most active seismic region in the world which is started from the west of Sumatera up to east of Papua. Nowadays, the reserves have been mined extensively in Batu Hijau, Nusa Tenggara Barat and Erzberg and Grasberg Papua. The goal of this paper is to present the results of Indonesian copper concentrate characterization for further education and research purposes.This characterization is considered important in determining metal extraction flow process for Indonesian copper concentrate. Materials that are used in this study are copper concentrates after flotation process. These copper concentrates, with mineralogical composition of chalcopyrite and pyrite, contain various precious metals, such as gold, silver, platinum, palladium, selenium, tellurium, and some other metals in several oxidation states. The characterization method includes chemical analysis using X-ray fluorescence spectroscopy (XRF) for basic metals and inductively coupled plasma mass spectrometry (ICP-MS) special for precious metals. While, X-ray diffraction (XRD) is used for the mineralogical phases. Subsequently, the element visualization in element sample was characterized by scanning microscopic with energy dispersive X-ray spectrometer (SEM-EDX) to analyse the condition of elements after treatments in certain temperatures.